Magnetic Memory: Magnetic Nanoplatelet‐Based Spin Memory Device Operating at Ambient Temperatures (Adv. Mater. 17/2017). Issue 17 (May 2017) - Koplovitz, Guy; Primc, Darinka; Ben Dor, Oren; Yochelis, Shira; Rotem, Dvir; Porath, Danny; Paltiel, Yossi
Abstract : In article number1606748, Yossi Paltiel and co‐workers use 30–50 nm ferromagnetic nanoplatelets (FMNPs) on top of an organic chiral molecule monolayer to demonstrate nano‐based magnetless magnetic memory device at ambient temperatures. The memory is based on the chiral induced spin selectivity effect. This technology could make it possible to create inexpensive, high‐density universal memory devices with much lower power consumption than existing technologies.